2005
DOI: 10.1515/znc-2005-1-205
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography-Mass Spectrometry Study of the Essential Oils of Schinus longifolia (Lindl.) Speg., Schinus fasciculata (Griseb.) I. M. Johnst., and Schinus areira L.

Abstract: The essential oil composition from the aerial parts of three Anacardiaceae growing in Bahía Blanca, Argentina was studied by gas chromatography and gas chromatography-mass spectrometry. The essential oils of S. longifolia and S. fasciculata have been studied for the first time. The major constituents were α-pinene (46.5%), -pinene (15.1%) and α-phellandrene (10.1%) for S. longifolia and limonene (10.9%), -phellandrene (6.16%) and α-phellandrene (5.6%) for S. fasciculata. The major components of the essential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 2 publications
2
5
0
1
Order By: Relevance
“…The essential oil composition of the Chilean species is similar to the major constituents described for Schinus longifolia essential oil (Murray et al, 2005) and differs from Patagonia species witch are similar to Schinus molle (Marongiu et al, 2004) Schinus fasciculata and Schinus areira essential oils, being most of them species from Argentina; as these contains nearly 58.3% of monoterpenes, being the major constituents ␣-phellandrene (12.9%) and limonene (22.6%) and 20.4% of sesquiterpenes being ␣-cadinol and cubenol the main compounds (7.1% and 5.6%, respectively).…”
Section: Chemical Constituents Of Essential Oilsupporting
confidence: 59%
“…The essential oil composition of the Chilean species is similar to the major constituents described for Schinus longifolia essential oil (Murray et al, 2005) and differs from Patagonia species witch are similar to Schinus molle (Marongiu et al, 2004) Schinus fasciculata and Schinus areira essential oils, being most of them species from Argentina; as these contains nearly 58.3% of monoterpenes, being the major constituents ␣-phellandrene (12.9%) and limonene (22.6%) and 20.4% of sesquiterpenes being ␣-cadinol and cubenol the main compounds (7.1% and 5.6%, respectively).…”
Section: Chemical Constituents Of Essential Oilsupporting
confidence: 59%
“…Chemical compositions of essential oil of S. areira from aerial parts (leaves and flowers) collected from Mendiolaza, Córdoba, Argentina revealed that the chromatographic profile was predominantly composed by monoterpenes compounds (66.4%); the main components were α-pinene (13.80%), limonene (12.81%) and camphene (12.62%) (Bigliani et al, 2012). Other chemical compositions of essential oils from aerial parts of S. areira were reported by Scrivanti et al (2003), Wannaz et al (2003) and Murray et al (2005). Extensive studies concerned with the chemical composition of EO isolated from S. molle have been reported (Marongiu et al, 2004;Hayouni et al, 2008;Atti dos Santos et al, 2009;Mendonça Rocha et al, 2012) showing the basic constituents α-phellandrene, β-phellandrene, myrcene and α-pinene.…”
Section: Introductionmentioning
confidence: 70%
“…S. molle (L.) (Anacardiaceae) is a highly aromatic evergreen tree, known as a source of essential oils with a pleasant spicy scent (Murray and others ; Gomes and others ). Its essential oils have antibacterial, antifungal, anti‐inflammatory, cytotoxic, insecticidal (Abdel‐Sattar and others ; Deveci and others ; López and others ), antioxidant, and antimicrobial properties (Martins and others ).…”
Section: Benefits Of Oils and Their Encapsulationmentioning
confidence: 99%